Peranan Koperasi Gabungan Kelompok Tani (GAPOKTAN) Bukit Barisan Dalam Meningkatkan Kesejahteraan Anggota Ditinjau Dari Ekonomi Islam: Studi Di Desa Sukarami Kecamatan Air Nipis Kabupaten Bengkulu Selatan - Yosy Arisandy (Al-Musthofa: Journal of Sharia Economics, 2018)
This Study aims to determine the role of Koperasi Gapoktan Bukit Barisan in improving the welfare of members and to know the review of Islamic Economics on the role of Koperasi Gapoktan Bukit Barisan in improving the welfare of members. The problems studied are (1) How does the Role Koperasi Gabungan Kelompok Tani (Gapoktan) Bukit Barisan In Improving Members Welfare? (2) How does the Islamic Economics Review on the Role of Gabungan Kelompok Tani (Gapoktan) Bukit Barisan In Improving Members Welfare? This research use desciptive qualitative approach. Subjects in this study are all members of Koperasi Gapoktan Bukit Barisan. Data collection techniques used was interviews, observation, and documentation. The result of the research shows that 1) the role of Koperasi Gapoktan Bukit Barisan Cooperative in improving the welfare of members is to assist in the field of farming business by providing loans such as fertilizers and other agricultural equipment. 2) Gapoktan Bukit Barisan Cooperative observed from Islamic Economics that is not in accordance with Islamic Shari'ah because Gapoktan cooperatives do not use ijab and qabul contract in lending goods and cooperatives Gapoktan still use the system of interest in each lending of goods.